Mimmy & Sophie stories / Miriam Cohen ; pictures by Thomas F. Yezerski. - Cohen, Miriam, 1926- (Frances Foster Books/Farrer Straus and Giroux, 1999)
Four stories about Mimmy, who is six, and her four-year-old sister Sophie; their momma, poppa, and grandparents, who emigrated from Russia; and their Brooklyn neighborhood during the Depression.